The EM algorithm and its implementation for the estimation of frequencies of SNP-haplotypes - Polańska, Joanna (Zielona Góra: Uniwersytet Zielonogórski)
A haplotype analysis is becoming increasingly important in studying complex genetic diseases. Various algorithms and specialized computer software have been developed to statistically estimate haplotype frequencies from marker phenotypes in unrelated individuals.
Keywords: algorithms; haplotypes; likelihood functions; gene frequency